Rising Sea Level: Flood Management in Coastal Cities - Schmidt Caballero, María del Rosario (My University, 2023)
Abstract— In recent years, numerous scientific studies have generated valuable data on rising sea levels. The primary reason for this is the Antarctic glaciers melting produced by climate change exacerbated by global warming. Consequently, coastal cities are grappling with the critical issue of floods, and how to approach this problem. This paper aims to introduce diverse approaches to managing floods, highlighting the strategies employed by different countries in addressing this pressing concern. It is expected that this paper might help raise awareness of the impact this topic embodies. Resumen— En los últimos años, estudios han revelado un incremento en el nivel del mar. La razón principal de este fenómeno se debe principalmente al derretimiento de los glaciares en la Antártida, producto del cambio climático y profundizado por el calentamiento global. Las ciudades costeras hoy en día deben afrontar esta problemática. A partir de la idea de que no todos los países poseen los mismos recursos ni tecnologías, en este artículo se abordarán las medidas de defensa que los distintos gobiernos han empleado para manejar las inundaciones. Se espera que este trabajo ayude a crear conciencia sobre el impacto que este tema engloba
Keywords: sea level; nivel del mar; coastal cities; Inundaciones; infrastructure; Infraestructura